Mobile phone addiction and social anxiety among Chinese adolescents: Mediating role of interpersonal problems - Wei, Junxiang; Dang, Jingping; Mi, Yang; Zhou, Min (Anales de Psicología / Annals of Psychology, 2024)
Objectives: Mobile phone addiction (MPA) has frequently reported to be correlated with psychological disorders such as depression, stress and anxiety among young population. However, the extent to which these factors are correlated with MPA and the potential mechanism underlying those relationships are conclusive. This study aimed to investigate the association between MPA level and social anxiety among Chinese adolescents, and examined the mediation effect of interpersonal problems between them. Methods: A sample of 1027 school-based students selected by a stratified-cluster random sampling method responded to questionnaires regarding MPA Index, Social Interaction Anxiousness Scale, Interpersonal Problems Inventory, and demographic variables. Spearman correlation and multiple linear regression analyses were performed to investigate the extent of the association between MPA and social anxiety, and Sobel test and bootstrapping sampling confirmed the mediating role of interpersonal problems. Results: Of all students in our study, 5.9% were MPA, and MPA score was positively correlated with social anxiety after controlled for demographic variables in the adjusted model. Multiple mediation regression analysis revealed that the interpersonal problem was a significant partial mediator between MPA and social anxiety. Conclusion: The MPA adolescents were a subgroup population who need to pay more attention to prevent social anxiety. Improving interpersonal problems might be an effective approach to deal with MPA-induced social anxiety in adolescents.